Physical activity and health-related quality of life in former elite and recreational cricketers from the UK with upper extremity or lower extremity persistent joint pain: a cross-sectional study - Bullock, GS; Collins, G; Peirce, N; Arden, NK; Filbay, SR (BMJ Publishing Group, 2019)
OBJECTIVE: To evaluate and compare physical activity (PA) and health-related quality of life (HRQoL) in former elite and recreational cricketers with upper extremity (UE), lower extremity (LE) or no joint pain. STUDY DESIGN: Cross-sectional cohort. SETTING: Despite the high prevalence of joint pain in former athletes, the impact of UE pain and LE pain on PA and HRQoL and potential differences between former recreational and elite athletes are poorly understood. PARTICIPANTS: 703 former cricketers aged ≥18 years (mean age 58.7, SD 12.9, played an average of 30 (IQR 20-40) seasons, 72% of whom had played at a recreational level) were recruited through the Cricket Health and Wellbeing Study and met eligibility requirements (UE pain, LE pain or no joint pain (defined as pain on most days of the past month)). PRIMARY AND SECONDARY OUTCOMES: The International Physical Activity Questionnaire-Short Form collected weekly metabolic equivalents (METS), while the Short-Form 8 collected physical (PCS) and mental (MCS) component scores. Kruskal-Wallis tests with Dunn's post-hoc and multivariable linear regressions were performed. RESULTS: Weekly METS were similar in former cricketers with UE pain (median (IQR) 2560 (722-4398)), LE pain (2215 (527-3903)) and no pain (2449 (695-4203), p=0.39). MCS were similar between groups (UE pain 56.0 (52.1-60.0); LE pain 55.2 (51.1-59.4); no pain 54.7 (50.7-58.7), p=0.38). PCS were more impaired in former cricketers with UE pain (49.8 (44.9-54.8)) or LE pain (46.7 (41.0-51.9)) compared with no pain (54.2 (51.5-56.9), p<0.0001). Former cricketers with LE pain reported worse PCS than those with UE pain (p=0.04). Similar relationships were observed in former elite and recreational cricketers. CONCLUSION: Despite impaired physical components of HRQoL in former cricketers with UE pain or LE pain, pain was not related to PA levels or mental components of HRQoL. Physical components of HRQoL were most impaired in those with LE pain, and findings were similar among former elite and recreational cricketers.